FACTORS RELATED TO PHYSICAL ACTIVITY IN ADOLESCENTS - Awaliyah, Siti Nurbayanti (Ikatan Perawat Maternitas Indonesia Provinsi Jawa Barat, 2025)
One form of healthy living behavior and improving the quality of life is by doing physical activity every day. In the current global situation, 1 in 4 adults and 81% of adolescents do not do enough physical activity. The group of adolescents to young adults (15-24 years) has an inactive lifestyle (lack of physical activity) of 52%. The impacts of lack of physical activity include obesity, insulin resistance, motor disorders, decreased brain function, cognitive function and triggering strokes, heart attacks and osteoporosis. This study aims to determine the factors related to physical activity in adolescents at Madrasah Aliyah As-Suurur Pameungpeuk, Bandung Regency. The research design used is quantitative with a cross-sectional approach. The total sample was 85 respondents. The sampling technique used was Stratified Random Sampling. Data collection using a questionnaire. The results showed that most respondents had low physical activity as many as 36 students (42.4%). Based on bivariate analysis, it was found that there was a significant relationship between the five factors with physical activity, including self-efficacy (p value = 0.013), motivation (p value = 0.005), friend support (p value = 0.016), perceived benefits (p value = 0.001) and perceived barriers (p value = 0.005). It is recommended that adolescents routinely do moderate to vigorous physical activity for at least 15-30 minutes per day and can limit the amount of time spent inactive. Suggestions for further research can examine other variables such as beliefs, environment, work and culture with physical activity to increase physical activity in all age groups.